Formulation and In-Vitro Evaluation of Floating Tablets of Ranitidine Hydrochloride Using HPMC and Chitosan - Sharma, Sanjay K; Mandowara, Sourabh; Saxena, Vaibhav; Jaimini, Manish; Chauhan, Bhupendra Singh (Asian Journal of Pharmaceutical Research and Development, 2014)
Floating drug delivery system is one of the promising routes for drugs delivery with an absorption window in the stomach or in the upper small intestine. Prolonged gastric retention improves bioavailability, reduces drug dose in comparison to conventional dosage form and beneficial for drugs which have solubility problem at high pH and unstable at high pH environment. In present investigation, an attempt was made to deliver Ranitidine hydrochloride via floating drug delivery system to the vicinity of absorption site by prolonging the gastric residence time of the dosage form. Floating tablet was prepared by direct compression method using different grades of HPMC and Chitosan and varying concentration of sodium bicarbonate alone and in combination with citric acid (gas generating) agents along with MCC or lactose alone as filler. Tablets were subjected to various evaluation parameters such as hardness, friability, thickness, tablet density, weight variation, assay, floating property study, swelling study, in vitro drug release study. It was revealed that tablets of all batches had acceptable physical parameters. From in vitro dissolution study tablets of batch F5 and F10 were selected as an optimum batches and evaluated for further parameter like effect of hardness on floating lag time, effect of position of paddle on drug release, treatment of dissolution data with different kinetic equations.